Prediction Method for Solar Power using Linear Regression and Fuzzy Logic - MOHD ABIDEN, NOOR IZZAH; ZAMBRI, NOR AIRA; Salim, Norhafiz; Abu Hassan, Omar (Progress in Engineering Application and Technology, 2021)
The world is running out of fossil energy sources. Because of this, we are searching for alternative energy sources for next generation energy needs. However, solar energy may be the best choice for the future world because solar energy is the most abundant renewable energy sources. Photovoltaic power is unpredictable and depends on solar irradiation and temperature. Therefore, a prediction method is required. The maximum error can be obtained using this prediction method. Fuzzy logic system was used to get the accurate value of power. With the help from fuzzy logic and linear regression, the maximum error will be shown accurately.